Analytical solutions of the space–time fractional Kadomtsev–Petviashvili equation using the (G’/G)-expansion method - Hassaballa, Abaker; Salih, Mohyaldein; Khamis, Gamal Saad Mohamed; Gumma, Elzain; Adam, Ahmed M. A; Satty, Ali (Frontiers in Applied Mathematics and Statistics, 2024)
This paper focusses on the nonlinear fractional Kadomtsev–Petviashvili (FKP) equation in space–time, employing the conformable fractional derivative (CFD) approach. The main objective of this paper is to examine the application of the (G’/G)-expansion method in order to find analytical solutions to the FKP equation. The (G’/G)-expansion method is a powerful tool for constructing traveling wave solutions of nonlinear evolution equations. However, its application to the FKP equation remains relatively unexplored. By employing traveling wave transformation, the FKP equation was transformed into an ordinary differential equation (ODE) to acquire exact wave solutions. A range of exact analytical solutions for the FKP equation is obtained. Graphical illustrations are included to elucidate the physical characteristics of the acquired solutions. To demonstrate the impact of the fractional operator on results, the acquired solutions are exhibited for different values of the fractional order α, with a comparison to their corresponding exact solutions when taking the conventional scenario where α equals 1. The results indicate that the (G’/G)-expansion method serves as an efficient method and dependable in solving the nonlinear FKP equation.